Засади (принципи) кримінального провадження як гарантії захисту прав, свобод та законних інтересів неповнолітнього потерпілого при проведенні досудового розслідування - Кочура, О. О.; Kochura, O. O.; ORCID: http://orcid.org/0000-0003-0638-2911 (Журнал східноєвропейського права. – 2016. – № 23. – С. 32-38, 2016)
В даній статті проведено дослідження засад (принципів) кримінального провадження України як гарантій захисту неповнолітнього потерпілого при проведенні досудового розсування. Зроблено спробу виділити низьку правових положень, що повинні забезпечувати підвищений захист прав та законних інтересів неповнолітніх потерпілих в окрему засаду (принцип) кримінального провадження.

The article deals with the principles of the criminal procedure guarantees for the protection of the person during the preliminary investigation, in particular the minor victim. The author described the essence of criminal procedural guarantees according to the scientific studies and analysis. The author analyzed criminal procedural guarantees which ensure the rights and legitimate interests of individuals and founded the system of procedural guarantees implementation to provide legal aid services in criminal proceedure of Ukraine, in particular the minor victim. A generalization of international legal standards on these issues was made. The author studied the definition of “principle of the criminal procedure” and considered their system in criminal procedural law of Ukraine. It has been found that the principles of the criminal proceedings are decisive, fundamental peremptory provisions on patterns and the most significant characteristics of the criminal process, causing their value as a means to protect human rights and freedoms, and for regulating the activity of bodies and officials engaged in criminal proceedings. The author made an attempt to allocate some legal provisions which shall provide an increased protection of the rights and legitimate interests of minor victims in a separate basis (principle) of the criminal proceedings. It is related to the interest of society to protect a child who was violated and a victim of a crime, but could return to a normal life and become later a law-abiding citizen. Therefore, the theoretical development principles increased rights and legitimate interests of minors in criminal proceedings, a clear definition of their content is important to develop national criminal procedural science. Solving these problems will not only improve legal protection of juvenile criminal process participants (from both the prosecution and the defense) but contribute to recommendations aimed at improving national criminal procedural legislation.

В данной статье проведено исследование принципов уголовного производства Украины как гарантий защиты несовершеннолетнего потерпевшего при проведении досудебного расследования. Сделана попытка выделить ряд правовых положений, которые обязаны обеспечить повышенную защиту прав и законных интересов несовершеннолетних потерпевших в отдельный принцип уголовного производства.
Principles of the Criminal Proceedings as Guarantees ofthe Rights, Freedoms and Legal Interests of a Minor Victim during the Pretrial Investigation
Кочура, О. О. Засади (принципи) кримінального провадження як гарантії захисту прав, свобод та законних інтересів неповнолітнього потерпілого при проведенні досудового розслідування [Електронний ресурс] / Кочура Олександра Олександрівна // Журнал східноєвропейського права. – 2016. – № 23. – С. 32-38. - Режим доступу: http://easternlaw.com.ua/uk/arxiv-nomerov/zhurnal-sxidnoyevropejskogo-prava-23.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; гарантії прав та свобод людини; засади кримінального провадження; принципи кримінального провадження; неповнолітній потерпілий; guarantees of human rights and liberties; principles of criminal procedure; minor victim; неповнолітні; minors; гарантии прав и свобод человека; принципы уголовного производства; несовершеннолетний потерпевший; несовершеннолетние